Mathematical Modelling of Pseudomonas aeruginosa L-forms Reveals Complex Interplay Between Host Defence Mechanisms and Putative Treatments - Spalding, Chloe; Shirgill, Sandeep; Taylor, Emma; Krachler, Anne-Marie; Jabbari, Sara (Frontiers in Systems Biology, 2022)
The bacterium Pseudomonas aeruginosa has been shown to undergo a morphological transition akin to L-forms under exposure to antibiotics, a process which may contribute to persistent infections. With the further consideration of antibiotic-resistance mechanisms, this transition renders the design of effective treatment strategies challenging. Through a mathematical model, we illustrate that additionally incorporating the complexities of the host immune response can render somewhat surprising predictions from the simulations. In particular, scenarios arise whereby the addition of a treatment strategy to directly target the L-forms results in a worsened infection, while in others this treatment could turn an antibiotic-resistant infection from persistent to treatable. The study highlights the importance of understanding the in vivo interplay between immune cells and pathogens for successful treatment design.